1995
DOI: 10.1080/09595239500185061
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholics' beliefs about responsibility for, and recovery from, their condition

Abstract: A study was carried out with a sample of in-patients and out-patients in an alcohol treatment programme examining beliefs about where responsibility lay for their condition and recovery from it. Brickman et al. [1] proposed a framework for understanding these beliefs consisting of four 'models'. In each model responsibility for causing the problem and for resolving it is considered either to lie with the individual or with other factors. The results indicated that the alcoholics' beliefs could not readily be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…This is consistent with findings for other behavioral problems. For example, when asked about substance-use and non-substance use psychological problems, those who conceptualize a problem as a bad habit/character flaw/personality problem/sin/moral failure rather than a medical/psychological disorder/disease/addiction are less likely to seek treatment (Cunningham et al, 1993; Moyers & Miller, 1993; West & Power, 1995a; Varney et al, 1995; cunningham, Blomqvist, & Cordingley, 2007; Cunningham et al, 1996). More specifically, those who believe biology causes a drug problem or mental illness have more favorable attitudes toward medication whereas those who believe environment causes mental illness have more favorable attitudes toward psychotherapy (Kuppi & Carpiano, 2006; Iselin & Addis, 2003; cunningham et al, 2007; Cunningham et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with findings for other behavioral problems. For example, when asked about substance-use and non-substance use psychological problems, those who conceptualize a problem as a bad habit/character flaw/personality problem/sin/moral failure rather than a medical/psychological disorder/disease/addiction are less likely to seek treatment (Cunningham et al, 1993; Moyers & Miller, 1993; West & Power, 1995a; Varney et al, 1995; cunningham, Blomqvist, & Cordingley, 2007; Cunningham et al, 1996). More specifically, those who believe biology causes a drug problem or mental illness have more favorable attitudes toward medication whereas those who believe environment causes mental illness have more favorable attitudes toward psychotherapy (Kuppi & Carpiano, 2006; Iselin & Addis, 2003; cunningham et al, 2007; Cunningham et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Although multi-item scales have been developed to measure perceived causes of the inability to change (Humphreys et al, 1996; Luke, Ribisl, Walton, & Davidson, 2002; Schaler, 1995; West & Power, 1995b), none covered all of the causes we wished to examine nor was adaptable to different problems, plus all were lengthy. Thus, we employed single terms that have been used in prior studies of conceptualizations of tobacco and alcohol use and dependence (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…by Best (1995), many agree that addiction is to some extent and in some sense a socially constructed problem. Thus West (2007), for example, contends that addiction is a social construct with fuzzy borders, yet a condition in which many underlying pathologies and abnormalities become manifest. Put in a different way, even if addiction is not "just" an invention by powerful claims makers, the ways in which a "deviant" substance use or behaviour is defined, how such deviances are reacted to by society, and -thereby -the consequences to the individual of her/his deviance, as well as the long-term trajectory of her/his condition, are strongly influenced by norms and traditions that vary with time and place (Blomqvist 1998a).…”
Section: Introductionmentioning
confidence: 99%
“…West and Power (1995) observed that none of the models fit very well with client views on their alcohol dependence. Instead, clients tended to support many kinds of causal attributions.…”
Section: Previous Researchmentioning
confidence: 90%